Long-Term Influence of PCB- and PBDE-Spiked Microplastic Spheres Fed through Rotifers to Atlantic Cod (Gadus morhua) Larvae - Bogevik, André S.; Puvanendran, Velmurugu; Vorkamp, Katrin; Burgerhout, Erik; Hansen, Øyvind; Fernández-Míguez, María; Krasnov, Aleksei; Afanasyev, Sergey; Høst, Vibeke; Ytteborg, Elisabeth (International journal of molecular sciences, 2023)
Omnipresent microplastics (MPs) in marine ecosystems are ingested at all trophic levels and may be a vector for the transfer of persistent organic pollutants (POPs) through the food web. We fed rotifers polyethylene MPs (1–4 µm) spiked with seven congeners of polychlorinated biphenyls (PCBs) and two congeners of polybrominated diphenyl ethers (PBDEs). In turn, these rotifers were fed to cod larvae from 2–30 days post-hatching (dph), while the control groups were fed rotifers without MPs. After 30 dph, all the groups were fed the same feed without MPs. Whole-body larvae were sampled at 30 and 60 dph, and four months later the skin of 10 g juveniles was sampled. The PCBs and PBDEs concentrations were significantly higher in MP larvae compared to the control larvae at 30 dph, but the significance dissipated at 60 dph. Expression of stress-related genes in cod larvae at 30 and 60 dph showed inconclusive minor random effects. The skin of MP juveniles showed disrupted epithelial integrity, fewer club cells and downregulation of a suite of genes involved in immunity, metabolism and the development of skin. Our study showed that POPs were transferred through the food web and accumulated in the larvae, but that the level of pollutants decreased once the exposure was ceased, possibly related to growth dilution. Considering the transcriptomic and histological findings, POPs spiked to MPs and/or MPs themselves may have long-term effects in the skin barrier defense system, immune response and epithelium integrity, which may potentially reduce the robustness and overall fitness of the fish.